A Historical Perspective On Experimental Acoustic Processing Systems At DRDC Atlantic - Osler, John; Pecknold, Sean; Inglis, Gary; Stoddard, Mark (Canadian Acoustics, 2017)
An enduring application of underwater acoustics has been the requirement to detect submarines. Defence Research and Development Canada – Atlantic Research Centre (DRDC Atlantic) has been leading Canadian efforts in anti-submarine warfare (ASW) and naval sonar for 75 years. Part of this research has included the development and implementation of maritime acoustic processing systems, an effort which is still being undertaken at DRDC Atlantic.